PENGARUH INTERMITTENT FASTING 16 JAM PER HARI (16:8) TERHADAP NYERI HAID PADA MAHASISWI FAKULTAS ILMU KESEHATAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Aulia Azzahra (2023)
A common complaint often experienced by adolescent girls during menstruation is menstrual pain or dysmenorrhea. Menstrual pain is pain caused by hormonal imbalances such as prostaglandins and progesterone caused by uterine contractions that attack each individual. This study aims to determine the effect of Intermittent Fasting 16 hours per day (16:8) on menstrual pain in female students of the Faculty of Health Sciences of Universitas Pembangunan Nasional "Veteran" Jakarta. Quasi-experimental studies were used as the design of this study using a nonequivalent control-group before-after design approach. The sampling technique used was non probability sampling with purposive sampling method involving 63 subjects who had complaints of menstrual pain. The research participants were divided into an intervention group and a control group. The intervention group received treatment in the form of Intermittent Fasting for 16 - 25 days. Before the intervention, the average menstrual pain was found to be 6,456+1,365, 6,554+1,461 in each intervention group and control group, but the difference was not statistically significant p=0,785 (>0,05). After the 16:8 Intermittent Fasting treatment, a significant difference (p=0,000, p<0,05) in mean menstrual pain was found between the two groups with lower mean menstrual pain in the intervention group (intervention group: 3,570+2,231, control group: 6,633+1,580).